Inovasi Helm Infanteri Terintegrasi Battlefield Management System Untuk Monitoring Area Pertempuran Secara Real-Time - Masril, Mardhiah; Ghaly Risyadi; Ruri Hartika Zain; Firdaus (LPPM-ITEBA, 2025)
This study aims to design and develop an Army infantry helmet system integrated with a Battlefield Management System (BMS) to support real-time monitoring of soldier conditions and combat strategies. The system integrates various sensors, including heart rate monitoring, hazardous gas detection (MQ-135), gyroscopic orientation (MPU6050), digital compass (HMC5883L), and GPS positioning (NEO-6M), managed by Arduino and NodeMCU microcontrollers. Sensor data is transmitted using LoRa communication modules and forwarded via the MQTT protocol to a monitoring system built with Grafana for real-time interactive dashboard visualization. The system is designed to provide periodic data on soldiers’ physical conditions and surrounding environments, aiming to enhance the speed and accuracy of strategic decisions on the battlefield. The prototype was tested in a simulated environment with a focus on sensor accuracy, transmission stability, and visualization reliability, showing promising results as an initial step toward IoT-based military monitoring and protection systems.